Problems with Officials Making Land Deeds in Collecting Fees for Acquisition of Land and Building Rights in Tegal City - Hariyono, Cipto (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
In property sale and purchase transactions, especially for buyers, a tax called BPHTB is imposed. The transaction for the transfer of rights to land and buildings is shown in the deed of sale made by the PPAT and the PPAT is the one who collects the BPHTB, but it is not uncommon to find many transactions for the transfer of rights to land and buildings carried out without using the services of a PPAT, only carried out underhand to avoid costs arising from the transfer of rights, including BPHTB. The purpose of this research is to examine the problems of Land Deed Officials in collecting Land and Building Acquisition Tax, and what are the obstacles and solutions of Land Deed Officials in collecting Land and Building Acquisition Tax. The approach method used in this legal research is an empirical legal approach method or in other words, it is called an empirical normative approach. In relation to the research method used, the author did this by researching legislation, regulations, legal theories and the opinions of leading legal scholars which are secondary data which are then linked to the actual situation, as well as related to problems found in the field related to problems faced by Land Deed Officials in collecting Land and Building Acquisition Tax. The results of the research obtained by the author include the contradiction in the BPHTB tax collection system, which was originally based on a self-assessment system, becoming an official assessment system. The validation process to determine the selling price of land and buildings is not regulated in laws and regulations, so that the process has an impact on changing the BPHTB value for a land object, automatically requiring more time.Keywords: Collection; Land; Selling.